Pengembangan Batik Ramah Lingkungan di Desa Tanjung Bumi: Penerapan Green Economy dan Tantangan Peningkatan Kapasitas Produksi - Wasil, Mohammad; Wibisono, R. Endro; Muzakki, Muzakki; Irmayanti, Nur (LPMP Imperium, 2026)
This Community Service Program (PKM) aims to provide solutions to the challenges faced by batik entrepreneurs, particularly Batik Jasminar in Tanjung Bumi Village, Bangkalan. The program focuses on the application of environmentally friendly technology and increasing production capacity through the use of automatic lorot machines. The lorot machine implemented in this program successfully speeds up the wax removal process from 30–40 minutes to just 10–15 minutes per piece of fabric. Additionally, the program includes training on the use of locally based natural dyes and digital marketing strategies, aimed at reducing reliance on synthetic dyes, enhancing the competitiveness of batik products, and expanding market reach. By applying appropriate technology and improving craftsmen's skills, it is expected that local batik products will be able to compete in both domestic and international markets with better quality, environmentally friendly processes, and greater innovation. This program also has a positive impact on improving quality, cost efficiency, and more sustainable business management. Ongoing evaluation and mentoring are required to ensure the sustainability and long-term positive impact on batik artisans in the Indonesian village.